Animal studies : the key concepts - Calarco, Matthew, 1972- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Prefaced with a brief introduction to the field of animal studies, the text explores the key influential terms, topics and debates which have had a major impact on the field, and that students are most likely to encounter in their animal studies classes. The book will be a valuable guide to undergraduate and postgraduate students in geography, philosophy, sociology, anthropology, women's studies, and other related disciplines. Seasoned researchers will find the book helpful, when researching topics outside of their specialization. Outside of academia, it will be of interest to activists, as well as professional organizations"--
List of key concepts -- Introduction -- THE KEY CONCEPTS -- Bibliography -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Zoology -- Encyclopedias; Human-animal relationships -- Philosophy -- Encyclopedias; Animals (Philosophy) -- Encyclopedias; Animal rights -- Encyclopedias; NATURE / Wildlife; PHILOSOPHY / General; SCIENCE / Earth Sciences / Geography